Photostabilization Efficiency of polymer nanocomposite: Functionalized Additives (International Journal of Food and Nutritional Sciences, 2022)
Multiwalled carbon nanotubes (MWCNTs) were effectively coated with a hindered amine light stabilizer (HALS). A study was conducted to examine how light-stabilizing MWCNTs affected the photo-oxidation behaviour of polyethylene (PE). MWCNTs were mixed in a solution to create the nanocomposites, which were then melted and compounded with polyethylene (PE). Polymer nanocomposites films were photo irradiated at 60°C for varying durations of time, with accelerated weathering conditions (λ > 290nm) applied. Transmission electron microscopy (TEM) and Fourier transform infrared spectroscopy (FTIR) were used to characterize the photo degradation. The homogeneous dispersion of the HALS functionalized polymer nanocomposite into a polymer matrix. Pure MWCNTs and HALS-f-MWCNTs/PE were contrasted. It was noted that during rapid weathering, the degree of photo degradation of HALS-f-MWCNTs was decreased. To achieve longer performances in outdoor conditions, functionalization of HALS onto the polymer backbone is often achieved.